Capture cross sections for heavy-ion reactions producing compound system with Z = 12 - N. A. Pilipenko; V. Yu. Denisov (Ядерна фізика та енергетика)
The fusion cross sections for reactions 50Ti + 249Cf, 54Cr + 248Cm, 58Fe + 244Pu and 64Ni + 238U are evaluated in the framework of simple barrier-penetration model, which takes into account quadrupole and hexadecapole surface deformations of nuclei.